N‐Terminal Protein Modification by Substrate‐Activated Reverse Proteolysis1. Issue 11 (12th February 2014) - Liebscher, Sandra; Schöpfel, Michael; Aumüller, Tobias; Sharkhuukhen, Ariunkhur; Pech, Andreas; Höss, Eva; Parthier, Christoph; Jahreis, Günther; Stubbs, Milton T.; Bordusa, Frank
Abstract Although site‐specific incorporation of artificial functionalities into proteins is an important tool in both basic and applied research, it can be a major challenge to protein chemists. Enzymatic protein modification is an attractive goal due to the inherent regio‐ and stereoselectivity of enzymes, yet their specificity remains a problem. As a result of the intrinsic reversibility of enzymatic reactions, proteinases can in principle catalyze ligation reactions. While this makes them attractive tools for site‐specific protein bioconjugation, competing hydrolysis reactions limits their general use. Here we describe the design and application of a highly specific trypsin variant for the selective modification of N‐terminal residues of diverse proteins with various reagents. The modification proceeds quantitatively under native (aqueous) conditions. We show that the variant has a disordered zymogen‐like activation domain, effectively suppressing the hydrolysis reaction, which is converted to an active conformation in the presence of appropriate substrates.